Memperkuat Pendidikan Islam di Era (Four Point Zero / 4.0) - Nanang Budianto; Khurin In Ratnasari (FALASIFA : Jurnal Studi Keislaman, 2020)
The industrial revolution has changed the way humans work that was originally completely manual now into automation / digitalization through innovation and thought that manifested in real form. The 4.0 revolution must be balanced with an education system and an increase in self-potential aimed at addressing the globalization era which is the character of the industrial revolution 4.0, the existence of the industrial revolution provides its own benefits for people's lives. Synthesis of the industrial revolution 4.0 will give birth to a prosperous society in development, while education has an important role in shaping future generations. With education it is expected to produce quality human beings, responsible and able to anticipate the future, especially in facing this era of the industrial revolution 4.0. Education in its broad meaning is always stimulating, accompanying the changes and development of humanity. In addition, educational efforts always lead, guide change and development of life and the lives of humanity in a better direction.